Effects of hydrogen clusters on interface facilitated plasticity at semi-coherent bimetal interfaces. (1st January 2021) - Wang, C.J.; Liu, Z.R.; Yao, B.N.; Kong, X.F.; Legut, D.; Zhang, R.F.; Deng, Y.
Abstract: Dislocation nucleation and interface sliding are two dominant plasticity events governing the mechanical behavior of metallic nanocomposites. Recent works have shown that both events can be closely related to atomistic interface geometries, however, how compositional factors, e.g., segregated hydrogen clusters, contribute both events are nearly unknown. Herein, we demonstrate that hydrogen clusters near misfit dislocation nodes can strongly suppress dislocation nucleation and interface sliding, while clusters at other positions will contribute somehow weaker effect on dislocation nucleation but facilitate interface sliding. These findings offer a rational atomistic mechanism for the effect of hydrogen clusters on interface facilitated plasticity. Graphical abstract: Image, graphical abstract